2011
DOI: 10.1002/macp.201000517
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth‐Triflate‐Catalyzed Polymerizations of ε‐Caprolactone

Abstract: εCL was polymerized using the triflates of lanthanum, samarium, magnesium, aluminum, scandium, and bismuth as catalysts. Bismuth triflate proved to be extraordinarily reactive, and catalyzed polymerizations of εCL even at 20 °C. Adding DTBMP reduced the polymerization rate only slightly. Furthermore, no evidence of a cationic mechanism was found by end‐group analyses. Polymerization at 20 °C either in bulk or in solution only yielded polyesters of low or medium molecular weights ($\overline {M} _{{\rm n}} $ up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…These results indicate that the direct calibration overestimates the real M n s by %30 and 45%, respectively in contrast to 80% in the case of poly(butylene succinate). [20] The DSC measurements of several homo-and copolyesters were conducted with a heating and cooling rate of 20 8C Á min À1 . All homo-and copolyesters were as expected, amorphous, and the glass transition temperatures (T g s) are listed in Table 1-3 and in the footnotes of Table 4.…”
Section: Sec and Dsc Measurementsmentioning
confidence: 99%
“…These results indicate that the direct calibration overestimates the real M n s by %30 and 45%, respectively in contrast to 80% in the case of poly(butylene succinate). [20] The DSC measurements of several homo-and copolyesters were conducted with a heating and cooling rate of 20 8C Á min À1 . All homo-and copolyesters were as expected, amorphous, and the glass transition temperatures (T g s) are listed in Table 1-3 and in the footnotes of Table 4.…”
Section: Sec and Dsc Measurementsmentioning
confidence: 99%
“…Secondly, bismuth halide and bismuth triflate were found to be efficient catalysts of the ring-opening polymerization of oxazolies [32] and e-caprolactone. [33][34][35] Therefore, the present work should expand our systematic studies of bismuth-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, for Bi 3+ ‐catalyzed polymerizations at room temperature, it was also observed that the Mn values increased upon prolonged storage, although the conversion of ϵ‐CL was completed within 2–4 d. (depending on the ϵ‐CL/water ratio) . This reproducible chain growth effect was speculatively attributed to condensation steps involving the CH 2 OH and the CO 2 H end groups.…”
Section: Resultsmentioning
confidence: 99%
“…Although this amount of water is very small, it may play a role for polymerizations with ϵ‐CL/water ratios >100. With regard to Mn and its dependence on the ϵ‐CL/water ratio, the results obtained here well agree with those found for Bi 3+ ‐catalyzed polymerizations …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation